PENGARUH CIPTA, RASA, KARSA, ASAS KEMANDIRIAN DAN PENGETAHUAN PERPAJAKAN TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK MENJADI KONSULTAN PAJAK - Figuna, Totok Agustian (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to determine the effect of creativity, taste, intention, the principle of independence, and knowledge of taxation on the interest of accounting students to become tax consultants. The results of this study indicate that Creativity, Taste, Intention, the Principle of Independence, and Knowledge of Taxation have a positive effect on the interest of accounting students to become tax consultants. This study uses a quantitative description method and primary data using a questionnaire. The number of samples in this study was 103 respondents from students of the 2018 and 2019 Accounting Study Programs, Universitas Sarjanawiyata Tamansiswa. Sampling in this study used a snowball sampling technique. Data was taken using a Google form questionnaire. This study shows that creativity, taste, and intention do not have a positive effect on the interest of accounting students to become tax consultants, while the principle of independence and knowledge of taxation have a positive effect on the interest of accounting students to become tax consultants.